(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
This article analyzes foreign experience in implementing tax administration of large taxpayers, and as a result of these analyzes, issues of improving the tax legislation of the Republic of Uzbekistan, proposals and recommendations for further improving tax administration of large taxpayers were developed.